Designing a better weather display. (July 2013) - Ware, Colin; Plumlee, Matthew D
Weather maps commonly display several variables at once, usually a subset of the following: atmospheric pressure, surface wind speed and direction, surface temperature, cloud cover, and precipitation. Most often, a single variable is mapped separately and occasionally two are shown together. But sometimes there is an attempt to show three or four variables with a result that is difficult to interpret because of visual interference between the graphical elements. As a design exercise, we set the goal of finding out if it is possible to show three variables (two 2D scalar fields and one 2D vector field) simultaneously so that values can be accurately read using keys for all variables, a reasonable level of detail is shown, and important meteorological features stand out clearly. Our solution involves employing three perceptual "channels": a color channel, a texture channel, and a motion channel in order to perceptually separate the variables and make them independently readable. We describe a set of interactive weather displays, which enable users to view two meteorological scalar fields of various kinds and a field showing wind patterns. To evaluate the method, we implemented three alternative representations each simultaneously showing temperature, atmospheric pressure, wind speed, and direction. Both animated and static variants of our new design were compared to a conventional solution and a glyph-based solution. The evaluation tested the abilities of participants both to read values using a key and to see meteorological patterns in the data. Our new scheme was superior, especially in the representation of wind patterns using the motion channel. It also performed well enough in the representation of pressure using the texture channel to suggest it as a viable design alternative.